Effectiveness and Safety of Ustekinumab in Ulcerative Colitis: Real-world Evidence from the ENEIDA Registry. (16th April 2021) - Chaparro, María; Garre, Ana; Iborra, Marisa; Sierra-Ausín, Mónica; Barreiro-de Acosta, Manuel; Fernández-Clotet, Agnès; de Castro, Luisa; Boscá-Watts, Maia; Casanova, María José; López-García, Alicia; Lorente, Rufo; Rodríguez, Cristina; et al.
Abstract: Background and Aims: The development programm UNIFI has shown promising results of ustekinumab in ulcerative colitis [UC] treatment which should be confirmed in clinical practice. We aimed to evaluate the durability, effectiveness, and safety of ustekinumab in UC in real life. Methods: Patients included in the prospectively maintained ENEIDA registry, who received at least one intravenous dose of ustekinumab due to active UC [Partial Mayo Score [PMS]>2], were included. Clinical activity and effectiveness were defined based on PMS. Short-term response was assessed at Week 16. Results: A total of 95 patients were included. At Week 16, 53% of patients had response [including 35% of patients in remission]. In the multivariate analysis, elevated serum C-reactive protein was the only variable significantly associated with lower likelihood of achieving remission. Remission was achieved in 39% and 33% of patients at Weeks 24 and 52, respectively; 36% of patients discontinued the treatment with ustekinumab during a median follow-up of 31 weeks. The probability of maintaining ustekinumab treatment was 87% at Week 16, 63% at Week 56, and 59% at Week 72; primary failure was the main reason for ustekinumab discontinuation. No variable was associated with risk of discontinuation. Three patients reported adverse events; one of them had a fatal severe SARS-CoV-2 infection. Conclusions: Ustekinumab is effective in both the short and the long term in real life, even in a highly refractory cohort. Higher inflammatory burden at baseline correlated with lower probability of achieving remission. Safety was consistent with the known profile of ustekinumab.